Dietary Lysozyme Alters Sow’s Gut Microbiota, Serum Immunity and Milk Metabolite Profile - Zhou, Jian; Xiong, Xia; Yin, Jia; Zou, Lijun; Wang, Kexing; Shao, Yirui; Yin, Yulong (Frontiers in Microbiology, 2019)
The aim of current study was to determine variations in sow’s gut microbiota, serum immunity and milk metabolite profile mediated by lysozyme supplementation. Twenty-four pregnant sows were assigned to a control group without supplementation and two treatments with 0.5 kg/t and 1.0 kg/t lysozyme provided in formula feed for 21days (n=8 per treatment). Microbiota analysis and metagenomic predictions were based on 16s RNA high-throughput sequencing. Milk metabolome was assessed by untargeted liquid chromatography tandem mass spectrometry. Serum biochemical indicators and immunoglobulins were also determined. Gut microbial diversity of sows receiving 1.0kg/t lysozyme treatment was significantly reduced after the trial. Spirochaetes, Euryarchaeota and Actinobacteria significantly increased while Firmicutes showed a remarkable reduction in 1.0kg/t group compared with control. Lysozyme addition rebuilt sow’s gut microbiota to beneficial composition identified by reduced richness of Escherichia coli and increased abundance of Lactobacillus amylovorus. Accordingly, microbial metabolic functions including Pyrimidine metabolism, Purine metabolism and Amino acid related enzymes were significantly up-regulated in 1.0kg/t group. Microbial metabolic phenotypes like the richness of gram-positive bacteria and oxidative stress tolerance were also significantly reduced by lysozyme treatment. Serum alanine transaminase (ALT) activity and IgA levels were significantly down-regulated in the 1.0 kg/t group compared with control, but IgM levels showed a significantly increase in 1.0kg/t group. Milk metabolites such as L-Glutamine, creatine and L-Arginine showed significantly dose-dependent changes after treatment. Overall, lysozyme supplementation could effectively improve the composition, metabolic functions and phenotypes of sow’s gut microbiota and it also benefit sows with better serum immunity and milk composition. This research could provide theoretical support for further application of lysozyme in promoting animal gut health and prevent pathogenic infections in livestock production.